Understanding sociodemographic factors influencing behaviour against littering in greenspace in Shah Alam, Selangor / Adlina Hayani Hamzaidi ... [et al.] - Hamzaidi, Adlina Hayani; Tengku Ibrahim, Tengku Nilam; Abdullah, Amir Heberd; W. Rasdi, Nadiah; Shafie, Farah Ayuni; Mohd Yatim, Siti Rohana (Faculty of Health Sciences, Universiti Teknologi MARA, 2024)
Despite its scientific relevance and importance for solid waste management and pollution control, studies on littering are incredibly underrepresented in the greenspace in Shah Alam and in most of developing countries. Urban greenspaces like national parks or woodland are subjected to various recreational impacts, including littering. The increased number of visitors to the parks has led to a rise in littering which poses pollution and being a significant environmental threat. To gain insight into people's littering habits, this study examined the relationship between sociodemographic background and littering behavior in Shah Alam, Selangor. An online cross-sectional survey was conducted to obtain information on the response of the public to littering and perception of cleaning responsibilities. Sociodemographic characteristics were found to have a significant relationship with littering. The results provided an overview of the sociodemographic effect on public littering behaviour and highlighted the possibility that an integrated litter prevention plan (social, cognitive, and technological) is the most efficient method to handle the problem of littering in Shah Alam. This study benefited by assisting the government in litter prevention and emphasizing the need to solve the litter problem in Shah Alam. This study highlighted the possibility that an integrated litter prevention plan is the most efficient method to handle the problem of littering in Shah Alam neighborhoods. Integrated techniques include social, cognitive, and technological tactics.